Implementation of Competence-Based Learning Approach: stories of practices and the Tuning contribution to academic innovation - Anna Serbati (Universidad de Deusto, 2015)
The rationale of the present paper is to investigate and stimulate a reflection on the Tuning contribution to academic innovation through the collection of case studies among some Tuning projects, focussing on methods and tools to implement successful and innovative approaches to learning, teaching, and assessment appropriate for competence-based approach (CBA). In order to deepen these concepts, a conceptual framework on competence-based approach and student-centred learning will be presented, particularly focussing teacher conceptions of teaching as well as pedagogical content knowledge and their influence on teaching practices. The Tuning contribution in supporting academic innovation will then be deepened, through a macro-level overview of the methodology, and a synoptic table of cross-cutting themes identified across the Tuning projects will be the starting point of the empirical part of this study. Moreover, the multiple case studies conducted through semi-structured interviews with teachers from Higher Education Institutes involved in previous completed Tuning projects will be presented. Research design, sampling and data analysis will be described, and major findings will be presented. Results show a general understanding, but with different perspectives on the competence based approach as well as appropriate teaching and learning methods applied worldwide within the CBA framework. Outlines on the Tuning contribution to academic innovation in this framework will be offered, by identifying main strengths, weaknesses, threats and opportunities of the methodology. Suggestions and guidelines for future projects, training and researches of the Tuning Academy are provided for possible implementation, highlighting the relationship between teaching, learning and research.